Dyanamic Capability Pesantren Entrepreneur - Heri Cahyo Bagus Setiawan; Nur Hidayat; Beni Dwi Komara; Sukaris; Aries Kurniawan (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
The dynamic capabilities approach examines how organizations build and maintain their competitive position in situations of rapid and unpredictable organizational change. Teece (2008) states that the dynamic capability component involved in shaping (not just adjusting) the environment is an entrepreneurial characteristic. This means that an organization with strong dynamic capabilities is highly entrepreneurial. Where they not only adapt the business ecosystem, but also shape it through innovation and collaboration with other organizations or companies and institutions. Based on the background and several studies from the literature that the author reviewed, and the model contained in Figure 1 in this research report, the authors are interested in conducting a study of dynamic capabilities in relation to how to realize and develop entrepreneurship-based pesantren, or in this paper it is called as a pesantrenpreneur. A new concept that can be developed into a new theory about how pesantrenpreneurs are developed through dynamic capabilities. Furthermore, this study brings theoretical implications and directions for future research. Keywords: Dynamic Capabilities, Pesantrenpreneur